2023
DOI: 10.1186/s13027-023-00558-z
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the clonal relationship of esophageal second primary tumors in patients with laryngeal squamous cell carcinoma

Meixuan Wan,
Xinxin Yang,
Lin He
et al.

Abstract: Laryngeal cancer ranks as the second most prevalent upper airway malignancy, following Lung cancer. Although some progress has been made in managing laryngeal cancer, the 5-year survival rate is disappointing. The gradual increase in the incidence of second primary tumors (SPTs) plays a crucial role in determining survival outcomes during long-term follow-up, and the esophagus was the most common site with a worse prognosis. In clinical practice, the treatment of esophageal second primary tumors (ESPT) in pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 94 publications
0
2
0
Order By: Relevance
“…Human Papillomavirus (HPV) infection leads to squamous cancers of the oropharynx, and more studies suggested that HPV infection is also relative to an increased risk of Laryngeal Squamous Cell Carcinoma (LSCC). 25 There is increasing evidence showing that LSCC is associated with HPV infection, but the role of HPV in LSCC has not been conclusively established. 25 , 26 Recent studies have shown that HPV infection is not only tightly associated with laryngeal cancer occurrence and progression but is also related to the sensitivity of oropharyngeal tumors to radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human Papillomavirus (HPV) infection leads to squamous cancers of the oropharynx, and more studies suggested that HPV infection is also relative to an increased risk of Laryngeal Squamous Cell Carcinoma (LSCC). 25 There is increasing evidence showing that LSCC is associated with HPV infection, but the role of HPV in LSCC has not been conclusively established. 25 , 26 Recent studies have shown that HPV infection is not only tightly associated with laryngeal cancer occurrence and progression but is also related to the sensitivity of oropharyngeal tumors to radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“… 25 There is increasing evidence showing that LSCC is associated with HPV infection, but the role of HPV in LSCC has not been conclusively established. 25 , 26 Recent studies have shown that HPV infection is not only tightly associated with laryngeal cancer occurrence and progression but is also related to the sensitivity of oropharyngeal tumors to radiotherapy. 27 Currently, the influence of HPV infection on the radiosensitivity of oropharyngeal tumors is controversial, and most studies have suggested that HPV-positive oropharyngeal tumors can increase radiosensitivity.…”
Section: Discussionmentioning
confidence: 99%